Pelaksanaan Putusan Hak Asuh Anak Dan Kepastian Hukumnya Terhadap Putusan Pengadilan Agama Ternate Nomor 623/Pdt.G/2020/PA - Ayu, Laras; Latupono, Barzah; Fataruba, Sabri (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The implementation of child custody decisions made by the Ternate Religious Court is in accordance with the positive law applicable in Indonesia, namely Law Number 1 of 1974 concerning marriage and the compilation of Islamic law (KHI).Purposes of the Research: This research aims to analyze the implementation of child custody decisions regarding the Ternate Religious Court Decision Number 623/Pdt.G/2020/PA.Tte and what obstacles the Ternate Religious Court faces in the process of implementing the decision. Methods of the Research: This type of research is normative law.Results / Findings / Novelty of the Research: The results obtained in writing this are; 1. Article 105 KHI explains that the right to custody of children under 12 years of age is the right of the mother, so the judge in the Ternate religious court in a decision with Register Number 623/Pdt.G/2020/PA.Tte dated 18 November 2020 granted the plaintiff's claim. and giving custody of the child (hadlannah) to the Plaintiff and in accordance with article 98 of the Compilation of Islamic Law regarding material care procedures, the defendant must pay for the child's education until the age of 21 years. 2. There are several obstacles in implementing the Decision with Register Number 623/Pdt.G/2020/PA.Tte, namely: a. The Respondent to the execution does not want to hand over the child to the Petitioner for the execution; b. The applicant for execution deliberately obstructed the execution, by threatening to carry out acts of violence if the child was taken by force; c. The child was deliberately hidden by the Respondent to the execution; d. The child himself did not want to accompany the Petitioner in the execution